UPAYA GURU DALAM MENGATASI KESULITAS BELAJAR SISWA - Buulolo, Tinusman (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2024)
This research is motivated by students being less motivated in following the learning process, students lack mastery of learning material and student learning outcomes are still low. The purpose of this study is to describe the efforts of teachers in overcoming student learning difficulties in class VII-B SMP BNKP Telukdalam. The results of the research found were teachers’ efforts in overcoming learning difficulties, namely providing remedial teaching (remidial), providing repetition activities for material (enrichment), forming group work for students, giving homework, explaining lessons back to students who do not understand, providing opportunities for students to ask questions, providing learning motivation, developing good attitudes and study habits towards students. Suggestions in this study are (1) To teachers, teachers to always try, look for factors, and make strategies in overcoming student learning difficulties that have been carried out by teachers so far. Teachers should improve in providing motivation or encouragement to students to be more active in proper learning. (2) Students should have attention to themselves, for example, if there is a problem that is difficult to solve alone, they should consult the teacher or others who can help solve the problem they face.